Improving the Performance of Posyandu Cadres with SIPPOS: Posyandu Service Information System in the Sangkali Tamansari Community Health Center Area Tasikmalaya City: Peningkatan Kinerja Kader Posyandu dengan SIPPOS: Sistem Informasi Pelayanan Posyandu di Wilayah Puskesmas Sangkali Tamansari Kota Tasikmalaya - Heni Sulastri; Siti Yuliyanti; Neng Ika Kurniati; Muhammad Al-Husaini; Hen Hen Lukmana (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2026)
Posyandu cadres have a strategic role in the promotion and prevention of public health services at the primary level. However, many cadres rely on manual recording systems that are less efficient. This community service focuses on training, mentoring, and monitoring the implementation of the system with the aim of improving the performance of Posyandu cadres through the implementation of SIPPOS (Posyandu Service Information System). SIPPOS is an information system to assist Posyandu cadres in managing health service data more quickly. Community service activities include SIPPOS socialization to cadres and health center officers, including training on system usage and technical assistance. Evaluation of the effectiveness of SIPPOS use in routine Posyandu activities, and program sustainability in order to expand the benefits of the community service reach. This community service is expected to significantly improve Posyandu cadres in mastery of information technology and the accuracy of service data recording.